REKONSTRUKSI PENDIDIKAN PESANTREN DALAM PEMBENTUKAN KADER ULAMA - Subhi, Imam (Universitas Islam Negeri Raden Intan Lampung, 2016)
The existence of pesantren’s education in Indonesiamakes people happy because its amount is rising andgrowing more and more. But, pesantren alsoundergo the change of educational system asgrowing era nowadays. A part of them keep theirsalafiyah educational style, and others standcooperatively with change. However, as pesantrenare growing rapidly, it appears a lot of problems andquestions, why is the rising number of pesantren notcomparable with the number of ulama cadresproduced? It is caused by some factors, they arepracmatic educational formalization, short studyingtime, dinamic societies' demands, and less spiritualapproaches. So, it needs some sistematicallyreconstructions, such as institutional reconstruction,the goal of pesantren itself and the curriculum. Thisis a part of innovation spirit and also sincerity tokeep pesantren's soul which is 'fort of producingulama cadres'. However, it agrees with the statement“almuhafadoh ala qodimissholih wal akhdudu biljadidil aslah'” (to keep old traditions and to take newbetter circumtances).